Теоретичні питання інформаційних джерел формування окремих методик розслідування кримінальних правопорушень - Голубов, А. Є.; Holubov, A. Ye.; ORCID: http://orcid.org/0000-0001-8608-4206 (Вісник Харківського національного університету внутрішніх справ. – 2021. – № 4 (95). – С. 199-208, 2021)
Наведено характеристику джерел формування окремих криміналістичних методик розслідування кримінальних правопорушень як їх інформаційної основи. Уточнено поняття, зміст, значення та систему таких джерел. Зроблено висновок, що системний підхід до формування та науково обґрунтовані аналіз і узагальнення змісту цих джерел є умовою розроблення ефективних сучасних методик розслідування кримінальних правопорушень.

The subject of the study is to provide a detailed description of the sources of formation of certain forensic methods of investigating criminal offenses. The purpose of the article is to clarify the concept, content, meaning and system of such sources. The main thesis of the scientific work is the assumption that the studied sources are objects, phenomena, processes that contain certain data, information, factual materials for the formation of certain forensic methods of investigating criminal offenses. In order to verify it, the analysis and generalization of the scientists’ views on this issue, considered the general theoretical foundations of forensic methodology, and more. The study is aimed at creating the preconditions for improving existing and developing new forensic recommendations. As a result, new scientifically substantiated results were obtained, which help to improve the provision of the investigative bodies, the prosecutor's office and the court with modern methodological recommendations aimed at improving the efficiency and completeness of the investigation and trial of criminal offenses. The study clarifies the cont ent of the concept of the source of certain methods of criminal offenses investigation (objects (phenomena, processes, etc.), which are the primary carriers of information for the formation of appropriate methods), their significance is determined (creation of scientifically substantiated information basis for formation of effective methods of investigation of criminal offenses) and their system is considered (theoretical, empirical, normative, analytical -informational and reference sources). It is proved t hat these sources form the information basis for the formation of certain methods of investigating criminal offenses. It is concluded that a systematic approach to the formation and scientifically sound analysis and generalization of the content of the system of these sources is a condition for the development of effective modern methods of investigating criminal offenses.

Приведена характеристика источников формирования отдельных криминалистических методик расследования уголовных правонарушений как их информационной основы. Уточнены понятие, содержание, значение и система таких источников. Сделан вывод, что системный подход к формированию и научно обоснованным анализу и обобщению содержания этих источников является условием разработки эффективных современных методик расследования уголовных правонарушений.
Theoretical issues of information sources for the formation of separate methods of investigating criminal offenses
Голубов, А. Є. Теоретичні питання інформаційних джерел формування окремих методик розслідування кримінальних правопорушень / Артем Євгенович Голубов // Вісник Харківського національного університету внутрішніх справ. – 2021. – № 4 (95). – С. 199-208. – DOI: https://doi.org/10.32631/v.2021.4.17.
Голубов, А. Є. (2021) «Теоретичні питання інформаційних джерел формування окремих методик розслідування кримінальних правопорушень», Вісник Харківського національного університету внутрішніх справ, 95(4), с. 199-208. doi: 10.32631/v.2021.4.17.
Keywords: Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Криміналістика. Criminalistics. Криминалистика; криміналістична методика; джерела криміналістичної методики; інформаційні джерела; окремі методики розслідування кримінальних правопорушень; розслідування кримінальних правопорушень; методики розслідування кримінальних правопорушень; криминалистическая методика; методики расследования уголовных правонарушений; forensic methodology; sources of forensic methodology; information base; separate methods of investigation of criminal offenses